Growth and prospect of halal food industry in Sabah : a case study of Sediabumi Yakin Sdn Bhd / Dasau Hassan and Rachellyinna Tanggau - Hassan, Dasau; Tanggau, Rachellyinna (2010)
This case study is the final requirement for final semester EMBA students or part-time mode at University Teknologi Mara (UiTM) for Master of Business Administration. It is a group orientated project requires strong cooperation among group members. A consultancy type of project research is the main aim of the paper whereby both theory and practical are combined together for the benefits of researchers. This report consists of five chapters: (1) An Introduction and Background of the Study, (2) Literature Review, (3) Case Study Methodology, (4) Finding and Analysis, and (5) Conclusion and Recommendations. This research is mainly about 'Growth and Prospect of Halal Food Products in Sabah: A case study of Sediabumi Yakin Sdn Bhd:' It serves three main purposes; to study the prospect of the food industry in Malaysia especially Sabah, the growth of the food industry particularly in Malaysia and at the global market in general and investigate the performance of the Sediabumi Yakin Sdn Bhd in Kota Kinabalu, It is important to understudy the existing players in the halal food industry just like Sediabumi Yakin Sdn Bhd. By doing the initial study the owner especially will get benefit prior to the completion of the study. We had identified certain area to be improved in the company as we had suggested in the recommendation. Besides, we found out that the market for halal food is huge not only in Malaysia but all over the world.